Deep Multi-Modal Transfer Learning for Augmented Patient Acuity Assessment in the Intelligent ICU - Benjamin Shickel; Benjamin Shickel; Anis Davoudi; Anis Davoudi; Tezcan Ozrazgat-Baslanti; Tezcan Ozrazgat-Baslanti; Matthew Ruppert; Matthew Ruppert; Azra Bihorac; Azra Bihorac; Parisa Rashidi; Parisa Rashidi; et al. (Frontiers Media S.A., 2021)
Accurate prediction and monitoring of patient health in the intensive care unit can inform shared decisions regarding appropriateness of care delivery, risk-reduction strategies, and intensive care resource use. Traditionally, algorithmic solutions for patient outcome prediction rely solely on data available from electronic health records (EHR). In this pilot study, we explore the benefits of augmenting existing EHR data with novel measurements from wrist-worn activity sensors as part of a clinical environment known as the Intelligent ICU. We implemented temporal deep learning models based on two distinct sources of patient data: (1) routinely measured vital signs from electronic health records, and (2) activity data collected from wearable sensors. As a proxy for illness severity, our models predicted whether patients leaving the intensive care unit would be successfully or unsuccessfully discharged from the hospital. We overcome the challenge of small sample size in our prospective cohort by applying deep transfer learning using EHR data from a much larger cohort of traditional ICU patients. Our experiments quantify added utility of non-traditional measurements for predicting patient health, especially when applying a transfer learning procedure to small novel Intelligent ICU cohorts of critically ill patients.